DESAIN KONSEPTUAL PLTN TERAPUNG DI INDONESIA TIMUR ASPEK KELAYAKAN DAN IMPLIKASI EKONOMI: Analisis Kelayakan dan Implikasi Ekonomi - Muhammad Hadid Kaharuddin; A. Muhammad Ikram; Muh. Asyhari Ramadhan; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2026)
Indonesia is a vast archipelagic country with thousands of islands stretching from west to east; however, the distribution and accessibility of electricity supply remain uneven across regions. This challenge necessitates reliable, sustainable, and affordable energy solutions, particularly in the eastern part of the country. To address the energy crisis and climate change mitigation, the Floating Nuclear Power Plant (FNPP) has emerged as a potential alternative due to its ability to generate large-scale electricity with low emissions, more efficient construction compared to land-based plants, and accessible cooling processes. This study evaluates the feasibility of implementing the FNPP design in the waters surrounding Halmahera Island, North Maluku Province. In addition to technical feasibility, the study also highlights economic implications, where the proposed 300 MW capacity not only has the potential to reduce energy disparities but also to provide affordable electricity (SDGs 7), support sustainable infrastructure development (SDGs 9), and promote the blue economy through enhanced access to electricity, strengthened fisheries, port activities, and the maritime industry. Accordingly, the conceptual design of the FNPP is expected to serve as a strategic solution to improve national energy security while supporting Indonesia’s sustainable development agenda. Furthermore, this design recommendation is anticipated to serve as a strategic reference to reduce energy disparities in remote areas, strengthen national energy resilience, and contribute to the global development agenda.